Islamic Art And Eschatology In The Kemas Community Dakwah At Media: An Quran Rhetorical Approach - Khairul Asyraf Mohd Nathir; Rosni Samah; Amani Nawi; Mohamad Yazid Abdul Majid; Bushro Abd Zaman (Maulana Malik Ibrahim State Islamic University, 2025)
Indexed